Feasibility and technical and economic design of thermal power cooling system to hybrid cooling system - Hamid Reza Ghanavati, Roozbeh Alipour, H. Nilsaz Dezfuli (International Journal of Advanced Science and Technology, 2020)
The consequences of the water crisis in terms of politics, social and environmental impacts led to the study of the dry / wet hybrid design of thermal power plant cooling systems of type wet cooling tower. The existence of consumer temperature constraints connected to the wet - tower of the steam power plant, Area constraints for the construction of auxiliary system, Pay attention to NPV over the project during the 25 year period, Returning the right capital, Optimum air cooler design and optimal performance over a year the reasons that led to the use of technical and economic analysis in this thesis was. The analyzes resulted in improving the air cooler based on its design at a single point of the year, will have the lowest initial costs and the lowest operating cost per year. Operating costs in this plan include: Water Consumption wet cooling tower, Air cooler fan, Wet tower fan. The results showed that the application of the system was considered, namely the location of the air cooler at the top of the wet tower. It was also reviewed over the course of one year, reducing 63 percent of water use and bringing back a five-year return on investment with a NPV of over 40 million euros. And eventually increased steam turbine power.